Numerical simulation of heat pipes in different applications - Hussein M. Maghrabie; A.G. Olabi; Abdul Hai Alami; Muaz Al Radi; Firas Zwayyed; Tareq salamah; Tabbi Wilberforce; Mohammad Ali Abdelkareem (International Journal of Thermofluids, 2022)
Nowadays heat pipes are considered to be popular passive heat transfer technologies due to their high thermal performance. The heat pipe is a superior heat transfer apparatus in which latent heat of vaporization is employed to transfer heat for an extended distance under a limited operating temperature difference. Numerical simulation of heat transfer devices is a principal step before implementing in real-life applications as many parameters can be tested in cost-and time-effective behaviors. The present study provides a review of the numerical simulations of various heat pipes in different applications such as cooling of electronic components, heating, ventilation, and air conditioning (HVAC), nuclear reactors, solar energy systems, electric vehicles, waste heat recovery systems, cryogenic, etc. Firstly, this work introduces a background about the main components of heat pipes such as an evacuated tube, wick, and working fluid. The fluid flow and thermal performance characteristics of heat pips are discussed, considering the optimum parameters. Finally, the critical challenges and recommendations for future work encountering the broad application of heat pipes are thoroughly studied.